Learning JavaScript data structures and algorithms: understand and implement classic data structures and algorithms using JavaScript - Groner, Loiane (PACKT Publishing, 2014)
Dictionaries and Hashes; Dictionaries; Creating a dictionary; The has and set methods; The remove method; The get and values methods; The clear, size, keys, and getItems methods; Using the Dictionary class; The hash table; Creating a hash table; Using the HashTable class; Hash table versus hash set; Handling collisions between hash tables; Separate chaining; Linear probing; Creating better hash functions